An Intrinsically Conductive Elastomer for Thromboembolism Diagnosis. Issue 2 (12th January 2021) - Tao, Xinglei; Yi, Wentian; He, Yonglin; Lyu, Shanzhi; Xu, Xiao‐Qi; Liao, Shenglong; Wang, Yapei
Abstract: As a minimally invasive procedure, balloon dilation is one crucial means to assist the delivery of stent and anti‐hyperplasia drugs to the embolism sites in the typical endovascular interventional treatments. However, it is rarely noted that the degree of balloon dilation is blurry, though it is extremely important to the efficiency of stent implantation, drug delivery, and even the postoperative recurrence rate of embolism. Herein, an innovative strategy of applying the balloon itself as an electrical sensor to monitor the dilation process is conceived. An intrinsically conductive elastomer formulated with polyurethane and potassium chloride is exploited as the biocompatible balloon, which integrates sufficient mechanical endurance, conductivity, biocompatibility, and pressure sensitivity against balloon expansion comprehensively. As a practical demonstration, the balloon sensor has been successfully applied to detect thrombus in tubular channels via real‐time pressure and temperature monitoring, which is anticipated to open an avenue to examine and treat cardiovascular diseases with a more controllable and reliable procedure. Abstract : A balloon‐shaped sensor with electric sensing ability is manufactured to monitor the slight pressure and temperature change in the cardiovascular system. The balloon is made from an intrinsically conductive elastomer which is conductive, elastic and biocompatible, rendering the possibilities of continuous dual‐signal detection in biological environments. The sensor is anticipated to assist the examination and treatment of cardiovascular diseases.